Overview of Risk Analysis as a Reach of Sustainable Construction - Nova Nevila Rodhi (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
The existence of construction projects has been considered a major source of environmental problems worldwide. However, basically the construction industry activities can make a positive contribution, this can be achieved if the whole process is carried out by taking into account the principles of sustainable development.To achieve a sustainable construction project requires a method that is effective and acceptable to all parties. Based on these problems, this study examines the integration of risk analysts to achieve sustainable construction using the literature review method.The results of this study indicate that there are 5 variables that affect the achievement of sustainable construction, namely social, environmental, economic, disaster and technical. The 5 variables are fully integrated in 2 forms of relationship, namely reinforcing and balancing, where these variables can strengthen each other, weaken each other and also balance each other. So that these variables can be integrated to achieve sustainable construction, some previous research results state that this can be achieved by risk analysis